Konsolidasi Demokrasi Sebagai Upaya Pembangunan Sistem Perdamaian Internasional dalam Teori Kantian - Pramesti, Adelisca; Zakky Almubaroq, Hikmat (Journal of Comprehensive Science, 2025)
Democracy has essentially contributed to building a climate of freedom, legal equality of subjects, organizing representative government, and separation of powers in the structure of state government institutions. In practice, democracy has also tried to build principles regarding the international peace order in the structure of government institutions among democratic countries in the world through the vision of peace after World War II and the Cold War. For that, how democratization efforts help accelerate the transition to democratic consolidation by designing institutions and maintaining norms and practices in democratic governance on the condition that they respect and protect minority rights. The principles of the international peace order aim to promote a vision of peace in the international arena, especially democratic countries to carry out interdependent relations in the global economic sector related to international trade and investment and welcome international bodies as executors of the democratization process. The presence of a vision of peace is capable of being an important supplement in answering the needs of democracy that provides protection, security and peace, as well as to ward off the tendency of military power and totalitarian government systems of other countries that hinder the practice of international peacebuilding. Thus, democracy in practice has created a widening opportunity for countries in the world to build a mutualistic symbiosis system regarding the rules of international order, especially the issue of economic relations with peace relations facilitated by international bodies.